2018
DOI: 10.1186/s12886-018-0796-0
|View full text |Cite
|
Sign up to set email alerts
|

Decreased choroidal thickness in vitiligo patients

Abstract: BackgroundVitiligo is a disease characterized by depigmented macules and patches that occur as a result of the loss of functional melanocytes from the affected skin through a mechanism which has not been elucidated yet. Destruction of pigment cells in vitiligo may not remain limited to the skin; the eyelashes, iris, ciliary body, choroid, retinal pigment epithelium and meninges may also be affected. This study aims to compare the choroidal thickness of patients with and without vitiligo using optical coherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 22 publications
3
31
1
Order By: Relevance
“…The lower SFCT in the cases is in line with the recent work by Demirkan et al, 17 although the mean SFCT in their cases was lower than the mean SFCT in our studied cases (221 μm and 252 μm, respectively); the same difference was found in our control groups. The different ethnicities of the study subjects in the two studies (Turkish population vs Egyptian population) may explain the difference in mean choroidal thickness measurements as ethnicity is reported to affect choroidal thickness.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The lower SFCT in the cases is in line with the recent work by Demirkan et al, 17 although the mean SFCT in their cases was lower than the mean SFCT in our studied cases (221 μm and 252 μm, respectively); the same difference was found in our control groups. The different ethnicities of the study subjects in the two studies (Turkish population vs Egyptian population) may explain the difference in mean choroidal thickness measurements as ethnicity is reported to affect choroidal thickness.…”
Section: Discussionsupporting
confidence: 93%
“…We could find two studies with ophthalmic assessment of vitiligo patients that included visual acuity comparisons with controls, and in both studies, the results showed that the difference was not statistically significant. 17,22 Furthermore, we correlated CDVA values with SFCT measurements and found a weak, albeit borderline statistically significant, correlation which could provide a possible explanation. Although this is a novel finding, the small sample size and the possibility of confounders dictate further assessments before arriving at any conclusions.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Demirkan et al found thinning in all choroidal layers in patients with vitiligo but stated that periorbital involvement had no effect on choroidal thickness 9 . Karabaş et al found that choroidal thickness in the subfoveal area was quite low in patients with oculocutaneous albinism 15 .…”
Section: Discussionmentioning
confidence: 99%